Development of a three dimensional visualization tool for spacecraft attitude and orbital dynamics using telemetry data - Abdelrahman, Mohammad (s.n, 2012)
Small satellite builders frequently encounter many different types of problems in testing different satellite subsystems at ground based laboratories. Full-scale testing can only be performed in orbit with actual flight systems, where critical errors sometimes cannot be resolved. Unlike huge budget missions, small satellite programs are supposed to have severe limitation in time, financial, and manpower resources. The future target of the project is to design, build, and test the mission software programs for spacecraft systems i.e., the ground control station computer and the on board computer.